2014
DOI: 10.5455/2320-6012.ijrms201408069
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic eye screening in multi ethnic population of Malaysia: epidemiological risk factors for development of diabetic retinopathy

Abstract: INTRODUCTIONDiabetic retinopathy is a dreadful sight threatening complication. Every part of the eye is susceptible to the harmful effects of diabetes.Diabetes mellitus affects various systems of our body including the eyes, kidneys and the peripheral nerves. Retinal damage caused by changes in diabetes known as Diabetic retinopathy is an important cause of blindness and visual disability in the working age group. The number of people with retinopathy increases as the diabetic population as well as diabetic ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…From the Logistic Regression equation, the odds of having diabetic retinopathy increased by 16.8% every year. This finding is consistent with the result of local study in which the patients with longer duration of DM had a higher risk of developing DR (Abougalambou & Abougalambou, 2015;Mallika et al, 2011;Mohd Ali et al, 2016;Naveen et al, 2014). The duration of diabetes seemed to be the strongest factor associated with the occurrence of retinopathy, as supported by several studies (Cardoso, Leite, Dib, & Salles, 2017;Casanova et al, 2014;Karadeniz & Yilmaz, 2007;Kim et al, 2018;Maria et al, 2003;Tsao et al, 2018).…”
Section: Resultssupporting
confidence: 88%
“…From the Logistic Regression equation, the odds of having diabetic retinopathy increased by 16.8% every year. This finding is consistent with the result of local study in which the patients with longer duration of DM had a higher risk of developing DR (Abougalambou & Abougalambou, 2015;Mallika et al, 2011;Mohd Ali et al, 2016;Naveen et al, 2014). The duration of diabetes seemed to be the strongest factor associated with the occurrence of retinopathy, as supported by several studies (Cardoso, Leite, Dib, & Salles, 2017;Casanova et al, 2014;Karadeniz & Yilmaz, 2007;Kim et al, 2018;Maria et al, 2003;Tsao et al, 2018).…”
Section: Resultssupporting
confidence: 88%
“…From those who presented with retinopathies, 21% aged of 40 years and above (Naveen et al, 2014). Data from diabetic eye registry in Malaysia showed that the prevalence of diabetic retinopathy was 36.8% and 14.7% of the patients had sight-threatening diabetic retinopathy (Goh et al, 2010;Squirrell & Talbot, 2003).…”
Section: Introductionmentioning
confidence: 99%